Determinação de elementos traços em poli-imida de alta pureza por amostragem de sólidos e espectrometria de absorção atômica com forno de grafite - Santos, Rafael Francisco dos (2015)
Polyimides are widely used in the industry for manufacture of crystal liquid displays, dielectric materials, and also for, aerospace applications, among others. Due to the several possibilities of application of polyimide, the quality control of this material is extremely important, making necessary the development of new methods for impurities determination. As well as for other polymers, the presence of trace amounts of metals may catalyze auto-oxidation reactions, affecting the characteristics of polymeric material. In this work it was proposed the use of solid sampling graphite furnace atomic absorption spectrometry for the determination of Cr, Cu, Mn, Na and Ni in polyimide. Pyrolysis and atomization curves were optimized using polyimide sample (BTDA-TDI/MDI) as well as reference solution. After this evaluation, the heating program for each analyte was stablished. Aqueous reference solutions were used for instrument calibration. A background correction system based on Zeeman effect was used.The linearity of calibration curves was higher than 0.99 and limits of detection were about ng g-1. For results comparison, polyimide (BTDA-TDI/MDI) was digested by dry ashing in a muffle furnace, microwave induced combustion (MIC) and by wet digestion using a single reaction chamber (SRC). Analytes determination in digests was performed by inductively coupled plasma optical emission spectrometry (ICP-OES). Results obtained for SS-GF AAS were compared with those obtained by ICP-OES after digestion by muffle furnace, MIC and SRC. No significant difference was found for Cr, Mn and Ni when compared to SRC, MIC and SS-GF AAS, while using muffle furnace the results were lower than limit of quantification. For SRC and MIC methods, the concentration of Cu and Na was lower than limit of detection impairing the comparison with SS-GF AAS.